Timing exchange rates using order flow: The case of the Loonie - King, Michael; Sarno, Lucio; Sojli, Elvira (Journal of Banking & Finance, 2010)
This paper examines the relation between the Canadian dollar/US dollar (CAD) exchange rate and foreign exchange order flow employing a novel data set on CAD order flow over the period 1994–2005. We investigate empirically the predictive information content and the determinants of order flow. The results suggest that order flow has strong out-of-sample predictive power for CAD returns, yielding significant market timing ability and tangible economic gains in a stylized dynamic asset allocation context. In terms of its determinants, order flow appears to reflect not only the menu of macroeconomic variables typically suggested in the literature but is also closely related to commodity price fluctuations, as expected from a ‘commodity currency’.